Hypopotassemia in Infantile Diarrhoea Treated With Half Strength Ringer's Lactate in Dextrose 2.5% - Purba, M. Djalinson; Loebis, Sjabaroedin; Purba, Djaman; Halim, Sahat; Sutanto, A. H.; Siregar, Helena (Paediatrica Indonesiana, 1982)
From October 15 until December 15, 1978, 13 children with acute enteritis admitted to the Pediatric ward, Pirngadi Hospital Medan and treated with i. v. half strength Ringer's lactate in Dextrose 2.5% had been evaluated for hypopotassemia. Criteria used were a serum potassium level of less than 4 mEq /L and the typical ECG pattern. Out of the 13 patients, 10 (79,6%) developed hypopotassemia during i. v. therapy. It is concluded that in cases of Pediatric gastroenteritis treated with half strength Ringer's lactate in Dextrose 2,.% the possibility of hypopotassemia should be seriously borne in mind.